2016
DOI: 10.1007/s00784-016-1861-9
|View full text |Cite
|
Sign up to set email alerts
|

Removal of simulated biofilm: an evaluation of the effect on root surfaces roughness after scaling

Abstract: All three tested instruments seem effective in the mechanical root debridement during SPT, whereat the ultrasonic device show the smoothest root surface of all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Conversely, no significant differences have been reported between the roughness parameters associated with hand instruments and ultrasonic piezoelectric scalers in a study analyzing the root surfaces of extracted teeth [8]. Differing results have also been obtained in studies comparing the effects of sonic and ultrasonic scalers [9,10]. Graetz et al [9] established that the ultrasonic scaler created a smoother surface than the sonic scaler or hand instruments, whereas Ribeiro et al [10] demonstrated that a sonic scaler with a diamond-coated tip and an ultrasonic scaler produced similar root-surface roughness, which was higher than that created with hand instruments.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, no significant differences have been reported between the roughness parameters associated with hand instruments and ultrasonic piezoelectric scalers in a study analyzing the root surfaces of extracted teeth [8]. Differing results have also been obtained in studies comparing the effects of sonic and ultrasonic scalers [9,10]. Graetz et al [9] established that the ultrasonic scaler created a smoother surface than the sonic scaler or hand instruments, whereas Ribeiro et al [10] demonstrated that a sonic scaler with a diamond-coated tip and an ultrasonic scaler produced similar root-surface roughness, which was higher than that created with hand instruments.…”
Section: Introductionmentioning
confidence: 97%
“…Differing results have also been obtained in studies comparing the effects of sonic and ultrasonic scalers [9,10]. Graetz et al [9] established that the ultrasonic scaler created a smoother surface than the sonic scaler or hand instruments, whereas Ribeiro et al [10] demonstrated that a sonic scaler with a diamond-coated tip and an ultrasonic scaler produced similar root-surface roughness, which was higher than that created with hand instruments. When we focused on the impacts of different ultrasonic instruments frequently used by professionals, we also found contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…If the A.actinomycetemcomitans challenge, especially A.actinomycetemcomitans of serovar-b, is not eliminated, through this tissue specific acute inflammatory response or/and the professional periodontal treatment, persisting in the periodontal crevice, severe tissue damage with a high rate of attachment loss and disease progression may occur ( 9 ), with a subsequent tooth loss at an early age and profound cosmetic, functional, and psychological effects ( 29 ). Multiple investigations demonstrated the effectiveness of sonic/ultrasonic devices in root surface debridement ( 30 , 31 ), with easier and faster root detoxification ( 17 ), disruption of the biofilm and reduction in the microbial load ( 16 ), producing a biologically compatible environment for reattachment/new attachment of adjacent periodontal tissues and their cells ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The burs resulted in cleaner surfaces with less calculus and smear layer than did the curettes, and tissue loss was less, but there were more instrumental marks and roughness was greater . Accordingly, in a recent in vitro study, a specific set of curettes, a piezo‐ceramic ultrasonic scaler and a sonic scaler were compared, and the smoothest root surfaces were obtained with the ultrasonic device …”
Section: Discussionmentioning
confidence: 99%